A Critical Moment,' Harper's Weekly caricature, 1904 (Harper & Brothers, 1904)
Issue of 'Harper's Weekly, A Journal of Civilization' (volume XLVIII (volume 48), no. 2481) political magazine featuring caricatures of William Jennings Bryan, a young William Randolph Hearst, Parker Gorman, Hill, and Olney all pulling on the Democracy personified as a cross-dressed man dressed in a dress and bonnet. The title reads as "A Critical Moment" with the reverse side sporting commentaries. Circa July 9th, 1904.